Epidemiology of benign paroxysmal positional vertigo: a population based study. Issue 7 (29th November 2006) - von Brevern, M; Radtke, A; Lezius, F; Feldmann, M; Ziese, T; Lempert, T; Neuhauser, H
Abstract : Objectives: To examine the prevalence and incidence, clinical presentation, societal impact and comorbid conditions of benign paroxysmal positional vertigo (BPPV) in the general population. Methods: Cross-sectional, nationally representative neurotological survey of the general adult population in Germany with a two stage sampling design: screening of 4869 participants from the German National Telephone Health Interview Survey 2003 (response rate 52%) for moderate or severe dizziness or vertigo, followed by validated neurotological interviews (n = 1003; response rate 87%). Diagnostic criteria for BPPV were at least five attacks of vestibular vertigo lasting <1 min without concomitant neurological symptoms and invariably provoked by typical changes in head position. In a concurrent validation study (n = 61) conducted in two specialised dizziness clinics, BPPV was detected by our telephone interview with a specificity of 92% and a sensitivity of 88% (positive predictive value 88%, negative predictive value 92%). Results: BPPV accounted for 8% of individuals with moderate or severe dizziness/vertigo. The lifetime prevalence of BPPV was 2.4%, the 1 year prevalence was 1.6% and the 1 year incidence was 0.6%. The median duration of an episode was 2 weeks. In 86% of affected individuals, BPPV led to medical consultation, interruption of daily activities or sick leave. In total, only 8% of affected participants received effective treatment. On multivariate analysis, age, migraine, hypertension, hyperlipidaemia and stroke were independently associated with BPPV. Conclusion: BPPV is a common vestibular disorder leading to significant morbidity, psychosocial impact and medical costs.